2016
DOI: 10.1007/s00122-016-2670-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships between race-nonspecific and race-specific interactions in the wheat–Pyrenophora tritici-repentis pathosystem

Abstract: We identified a major QTL conferring race-nonspecific resistance and revealed its relationships with race-specific interactions in the wheat- Pyrenophora tritici-repentis pathosystem. Tan spot, caused by the fungus Pyrenophora tritici-repentis (Ptr), is a destructive disease of wheat worldwide. The disease system is known to include inverse gene-for-gene, race-specific interactions involving the recognition of fungal-produced necrotrophic effectors (NEs) by corresponding host sensitivity genes. However, quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 44 publications
3
40
0
3
Order By: Relevance
“…Results from different studies, however, suggest the possible role of other genes and/or QTLs for three reasons. Second, there are different reports that suggest the complexity of the Ptr pathosystem in wheat (Chu et al, 2008a;Kariyawasam et al, 2016), which could be due to the role of other genes and/or QTLs. Second, there are different reports that suggest the complexity of the Ptr pathosystem in wheat (Chu et al, 2008a;Kariyawasam et al, 2016), which could be due to the role of other genes and/or QTLs.…”
Section: Marker-trait Association Analysismentioning
confidence: 99%
“…Results from different studies, however, suggest the possible role of other genes and/or QTLs for three reasons. Second, there are different reports that suggest the complexity of the Ptr pathosystem in wheat (Chu et al, 2008a;Kariyawasam et al, 2016), which could be due to the role of other genes and/or QTLs. Second, there are different reports that suggest the complexity of the Ptr pathosystem in wheat (Chu et al, 2008a;Kariyawasam et al, 2016), which could be due to the role of other genes and/or QTLs.…”
Section: Marker-trait Association Analysismentioning
confidence: 99%
“…This lack of association of the ToxA– Tsn1 interaction with disease demonstrates the complexities underlying the tan spot pathosystem, and may be due to the presence of race‐nonspecific resistance. Such a QTL was identified on chromosome 3B in a RIL population derived from a cross between a highly susceptible and a highly resistant wheat line (both sensitive to ToxA) (Kariyawasam et al ., ). The 3B QTL appeared to prohibit the effector‐triggered susceptibility from the ToxA– Tsn1 interaction, thus it appears that this QTL has an epistatic effect on the ToxA– Tsn1 interaction in certain host backgrounds.…”
Section: Introductionmentioning
confidence: 97%
“…Numerous studies have also reported quantitative resistance to P. tritici‐repentis that is effective against multiple races of the pathogen, thus deemed non‐race‐specific forms of resistance (Singh et al ., ; Faris et al ., ; Kariyawasam et al ., ). These studies highlight the complexity of host resistance to P. tritici‐repentis .…”
Section: Introductionmentioning
confidence: 97%